2015
DOI: 10.1016/j.renene.2014.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of natural dolomitic rock and waste mixed seashells as heterogeneous catalysts for the methanolysis of palm oil to biodiesel

Abstract: a b s t r a c tNatural dolomitic rock and waste mixed seashells were investigated as renewable sources for preparing heterogeneous catalysts for the methanolysis of palm oil to biodiesel as fatty acid methyl esters (FAME) at 60 C and ambient pressure. After calcination at 800 C, the dolomite as the mixed CaO$MgO catalyst possessed smaller CaO crystallites, a higher thermal stability and higher basicity than the pure CaO catalyst derived from the seashells. Although both catalysts gave the FAME yield >98% (w/w)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 29 publications
3
23
0
1
Order By: Relevance
“…The peaks of CaO (lime syn) appeared at 2θ = 32.38°, 37.52°, and 53.98° with (111), (200)and (220) orientations. In addition, Ca(OH) 2 (portlandite) also observed at 2θ = 18.16° and 34.26° due to hydration of CaO by atmospheric moisture[10]. These XRD result proves the calcination temperature of clamshell, 900 °C for 3.5 hours was suitable to completely decompose CaCO 3 into CaO.…”
mentioning
confidence: 66%
“…The peaks of CaO (lime syn) appeared at 2θ = 32.38°, 37.52°, and 53.98° with (111), (200)and (220) orientations. In addition, Ca(OH) 2 (portlandite) also observed at 2θ = 18.16° and 34.26° due to hydration of CaO by atmospheric moisture[10]. These XRD result proves the calcination temperature of clamshell, 900 °C for 3.5 hours was suitable to completely decompose CaCO 3 into CaO.…”
mentioning
confidence: 66%
“…2(b), the crystal structure changed and pores were observed. This provides a larger specific surface area of the catalyst which is an important characteristic of heterogeneous catalysts [21][22][23][24].…”
Section: Results and Discussion 31 Catalyst Characterizationmentioning
confidence: 99%
“…revealed that MgO in the calcined dolomite exhibited the inert activity in catalyzing transesterification but MgO promoted the catalytic activity of CaO as supporter . However, dolomite as catalyst is inherent with weaknesses of the low specific surface area, weak basic strength and active sites leaching trueCaMg(CO3) 2CaO+MgO+2CO2 …”
Section: Introductionmentioning
confidence: 99%
“…[17] However, dolomite as catalyst is inherent with weaknesses of the low specific surface area, weak basic strength and active sites leaching. [18]…”
Section: Introductionmentioning
confidence: 99%